2006
DOI: 10.1021/cm061686i
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Selective Synthesis of Copper Sulfide Nanocrystals

Abstract: Monodispersed copper sulfide nanocrystals were synthesized via the decomposition of an air-stable precursor, copper (I) thiobenzoate (CuTB), in the presence of dodecanethiol (DDT). We discover that, by varying the stabilizing agent used (trioctylphosphine or tributylphosphite), we can selectively generate phase-pure roxbyite nanoplates (Cu 1.75 S) or chalcocite faceted nanocrystals (Cu 2 S). We also demonstrate that, under suitable conditions, the roxbyite nanoplates can be forced to grow only in two dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 66 publications
5
96
1
Order By: Relevance
“…When the temperature of 200 • C was applied for the injection of DDT, hexagonal Cu 2 S nanodisks with larger size were finally achieved (see Supporting information, Fig. S3), which is similar to the results of the reports as referred [23,27,28]. It was found that if the nucleation temperature was set at a higher temperature (200 • C), while growth temperature was set at a lower temperature (such as 180 • C), uniform spherical Cu 2 S nanocrystals could be obtained even the reaction last for several hours.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…When the temperature of 200 • C was applied for the injection of DDT, hexagonal Cu 2 S nanodisks with larger size were finally achieved (see Supporting information, Fig. S3), which is similar to the results of the reports as referred [23,27,28]. It was found that if the nucleation temperature was set at a higher temperature (200 • C), while growth temperature was set at a lower temperature (such as 180 • C), uniform spherical Cu 2 S nanocrystals could be obtained even the reaction last for several hours.…”
Section: Resultssupporting
confidence: 86%
“…Various Cu 2 S nanostructures such as nanoparticles, nanodisks, nanowires, nanorods, and hexagonal nanoplates have been synthesized by various methods. Recently assembled structures [20][21][22][23][24][25][26][27][28]. For instance, Qian's group prepared ultrathin Cu 2 S nanowire by thermal decomposition of CuS 2 CNEt 2 in a mixture of DDT and oleic acid [21].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Especially their strong NIR absorption effect by LSPR. This LSPR property can be tunable by manipulating copper deficiency via controlling oxidation/reduction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these promising applications, several synthetic methods have been developed to produce nanoscale and micron scale metal chalcogenide nanoparticles including decomposition reactions [20], hydrothermal [21], microemulsions [22], thin films [23], and electrochemical deposition [24]. However, control over composition, shape, and impurities remains a challenge.…”
Section: Introductionmentioning
confidence: 99%